Mechanisms of Racial Health Disparities: Relationships between Coping and Psychological and Physiological Stress Responses - Allen, Julie Ober (Ethn Dis, 2020)
OBJECTIVE: Psychological distress and physiological dysregulation represent two stress response pathways linked to poor health and are implicated in racial disparities in aging-related health outcomes among US men. Less is known about how coping relates to these stress responses. The purpose of this exploratory study was to examine whether midlife and older men’s coping strategies and behaviors accounted, in part, for Black-White disparities in men’s psychological and physiological stress responses. METHODS: We examined racial differences in 12 coping strategies (COPE Inventory subscales, religious/spiritual coping, and behaviors such as stress eating and substance use) and their relationships with psychological distress (Negative Affect scale) and physiological dysregulation (blunted diurnal cortisol slopes) using regression models and cross-sectional data from 696 Black and White male participants aged 35-85 years in the National Survey of Midlife Development in the United States (MIDUS) II, 2004-2006. RESULTS: Black men exhibited more psychological distress and physiological dysregulation than White men. Black and White men reported comparable use of most coping strategies, none of which demonstrated similar relationships with both stress responses. Coping strategies explained variations in psychological distress consistent with conventional protective-harmful categorizations. Coping accounted for racial disparities in men’s psychological distress, as Black men reported using harmful strategies more often and were more susceptible to their negative effects. Neither differential use of coping strategies nor differing relationships accounted for racial disparities in physiological dysregulation. CONCLUSIONS: Findings revealed complex relationships between coping and psychological and physiological stress responses and suggest the importance of differing approaches to reducing associated racial health disparities among men.